THE ROLE AND PLACE OF BUDDHISM IN THE SOCIO-POLITICAL AND CULTURAL LIFE OF THE PEOPLES OF CENTRAL ASIA IN THE EARLY MIDDLE AGES - Sayyora Melisovna Atadjanova (Journals Park Publishing, 2023)
In this article, on the basis of sources and literature, the role of Buddhism in the socio-political and cultural life of the peoples of Central Asia is analyzed. The issues of the interaction of religious faiths that existed on the territory of the Middle of Asia in the early Middle Ages are considered, such as Christianity, Judaism, Zoroastrianism, Buddhism, as well as religious beliefs such as the teachings of Mani and others.
Keywords: traveler, ancient monuments, Mani's teaching, Buddhism, Zoroastrianism, monastery, church, temple.